Nanosuspension technology in salicylic acid and its particle size characterization - Ab. Hadi, Hazrina; Awadh, Ammar Ihsan Jawad (2015)
Salicylic acid (SA) is known to have keratolytic activity for the treatment of skin related disease such as acne and psoriasis. However, it usually causes side effects such as skin irritation. Also, SA is poorly soluble in water making it difficult to formulate. This study aims to explore the use of nanosuspension technology in enhancing the solubility of SA in aqueous solutions and provide a control release to reduce the side effects of salicylic acid by reducing its particle size into nanometer scale. This research project focused on the use of oil-in-water emulsification followed by solvent evaporation technique. The use of different amounts of ethyl acetate will be evaluated. This technique was chosen as it has high drug solubilization and capable of producing large scale because of simple manufacturing method and using low-cost materials. The manipulation of different amount of organic solvent, ethyl acetate has an impact in the particle size. Result shows that increase amount of ethyl acetate give smaller average particle size. However, the particle size increases after the process of centrifugation and freeze-drying. The percentage yields of the final products were shown to be low (below 25%). The study has shown that it is possible to reduce the particle size of SA to a nano-sized diameter. Thus the solubility of salicylic acid can be enhanced. However, more extensive research should be done to provide a more concrete conclusion. An improved understanding of the formulation factors will further advance the value of nanosuspension in topical drug delivery.